Chronic Otitis Media and Hearing Loss in Nepalese School Children (Global Journal of Medical Research, 2023)
Background Chronic otitis media is one of the leading causes of avoidable hearing loss in children in developing countries Early diagnosis and management of chronic otitis media can prevent hearing loss and the consequences that follow These include delayed language development poor academic performance and lifelong socioeconomic impacts Objectives To find out the prevalence of chronic otitis media in school-aged Nepalese children and to evaluate associated hearing loss Methods This is a retrospective study conducted by reviewing the screening records of schoolbased ear health programs conducted by our institute over a five-year period Medical records of children diagnosed with chronic otitis media were studied and segregated Data including diagnoses tympanic membrane findings and pure tone audiogram reports were documented and analyzed
Keywords: chronic otitis media; hearing loss; schoolchildren; nepal